2008
DOI: 10.1177/0162243907306702
|View full text |Cite
|
Sign up to set email alerts
|

Overseeing Research Practice

Abstract: This article examines whether and how a particular research practice is overseen and supervised, and by whom. This investigation fills notable gaps in the literature on science, including a lack of emphasis on larger sociopolitical structures, a neglect of regulation, and indifference toward ethics. The author focuses on the oversight of a particular research practice; data editing; which embodies qualities that are intriguing to sociologists of science: invisibility, uncertainty, heterogeneity, and reliance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In sum, provenance requires more than a bias assessment that measures predictive accuracy across protected groups. In particular, far less attention has been paid to how complex social realities are transformed into algorithmic systems and the normative assumptions that drive these processes 125–127. For example, rather than define ‘fairness’ as a fixed attribute, the literature we reviewed emphasised that it is a value-laden social and political determination made by individuals or groups of people within specific contexts.…”
Section: Resultsmentioning
confidence: 99%
“…In sum, provenance requires more than a bias assessment that measures predictive accuracy across protected groups. In particular, far less attention has been paid to how complex social realities are transformed into algorithmic systems and the normative assumptions that drive these processes 125–127. For example, rather than define ‘fairness’ as a fixed attribute, the literature we reviewed emphasised that it is a value-laden social and political determination made by individuals or groups of people within specific contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Some specific data preparation tasks with close affinities to statistical theory (especially missing data) have developed a substantial research literature, but the overall process of preparing data for analysis remains somewhat ad hoc and without a general methodological literature. Future empirical research might build on existing studies of researcher beliefs about data preparation (Leahey et al 2003;Leahey 2008) by studying regularities in the process of data preparation and quantifying the impacts that data preparation decisions have on estimates. Complementary theoretical research might enrich the connections between stages in the data pipeline and show how data preparation choices can be as important as data collection and modeling choices.…”
Section: The Future Of Metadata Systemsmentioning
confidence: 99%
“…Scientific norms are still emerging for data management and data deposit. For example, Leahey (2008) found that social scientists lack shared norms for editing data. Granted, many centralized resources do exist to guide the process of managing and depositing qualitative data.…”
Section: Introductionmentioning
confidence: 99%